Preparation and Aromatic Hydrocarbon Removal Performance of Potassium Ferrate - Wei Guan; Zhigang Xie; Jia Zhang (Journal of Spectroscopy)
This experiment adopts the hypochlorite oxidation method to constantly synthesize potassium ferrate. Under the condition of micropolluted source water pH and on the basis of naphthalene, phenanthrene, and pyrene as research objects, the effects of different systems to remove aromatic hydrocarbons were studied. Various oxidation systems to remove phenanthrene intermediate are analyzed and the detailed mechanisms for removal of phenanthrene are discussed. The study found that the main intermediate of potassium ferrate system to transform phenanthrene is 9,10-phenanthraquinone and its area percentage reached 82.66%; that is, 9,10-phenanthraquinone is the key entity to remove phenanthrene.